Pengaruh Budaya Kerja Positif Terhadap Kinerja Toyota Indonesia - Richard Michael Duncan; Ellian Danica Ekaristie; Erica Adriana (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to investigate the effect of a positive work culture on the performance of Toyota Indonesia. A positive work culture is an important aspect of creating a supportive, motivated and productive work environment. In this study, a literature study research methodology approach was used to collect and analyze the relevant literature on this topic. Result of this study show that a positive worplace culture has a significant influence on the production of Toyota Indonesia. Work culture creates a positive environment where employees feel valued, engaged and motivated to give their best contribution. This has a positive impact on employee engagement, effective teamwork, innovation and employee retention. This study emphasizes that a positive work culture has been revealed to be important to organizational performance. Toyota Indonesia can take advantage of these findings by building and strengthening a positive work culture throughout the organization. Thus, companies can increase employee engagement, effective work teams, innovation, and employee retention, which in turn will have a positive impact on the performance of the entire company.